Investigação das características das memórias autobiográficas e a utilização de pistas familiares - Correia, Warley Lamartine (2021)
Autobiographical memory (MA) encompasses knowledge about oneself and memories of specific personal events. These personal memories are topics that are often shared in social interaction, and their richness of details facilitates intimacy and allows the listener to relate to the story being told. On the other hand, the retrieval of AMs is influenced by emotions and the cues / stimuli used in the recovery process. It is known that MAs evoke other MAs, in an associative process, but the influence of the characteristics of the cues / stimuli used, such as their familiarity or self-reference, remains controversial. Thus, the objective of this work was to investigate the effect of specific familiar autobiographical memories, and of another subject of the same sex, on the affection and recall of other autobiographical memories. Specific autobiographical memories by audio exposure, were used, three of them from the volunteer himself and three standardized recordings of a subject with sex equivalent to the volunteer, in a total of six memories, two of positive valence, two negative and two neutral, and the positive and negative affect scale. The sample consisted of 23 healthy volunteers, aged between 18 and 30 years (M = 24.69, SD = 6.33). The data obtained were tabulated and analyzed using the Statistical Package for the Social Science software (SPSS 220.0). The results showed that hearing your own MA or that of another person of the same sex, predominantly recall other specific MAs and of the same valence as the MA used as a stimulus. There was no difference in the latency and specificity of the AMs between valences and conditions. However, it was observed that listening to a negative autobiographical memory, whether yours or that of another person of the same sex, promoted a longer duration of the narrative of negative autobiographical memories than the duration of the report of positive memories retrieval by other positive memories of the subject himself. There was also a reduction in positive affect. The data suggest that self-referential information from the self is an important aspect in the processing of personal information from autobiographical memories, but it is possible that the specificity and not the familiarity of the stimulus is related to access to other specific autobiographical memories. The results of the present study strengthen the model of the associative network of memories, the principles of specific retrieval and the relationship between memories and emotions, considering that the evocation of memories is a tool for emotional regulation.